Ethical prioritization of patients during disaster triage: A systematic review of current evidence. (March 2019) - Ghanbari, Vahid; Ardalan, Ali; Zareiyan, Armin; Nejati, Amir; Hanfling, Dan; Bagheri, Alireza
Highlights: Various medical and nonmedical measures should be considered in patient prioritization at the time of disaster triage. Differences in viewpoints about nonmedical measures should be used in the prioritization of patients are considerable. Despite the fact that most disaster victims are in underdeveloped or developing countries, most of the evidence about the ethical aspect of patients prioritization is published by researchers from developed countries. Abstract: Introduction: Triage is a dynamic and complex decision-making process in order to determine priority of access to medical care in a disaster situation. The elements which should govern an ethical decision-making in prioritizing of victims have been debated for a long time. This paper aims to identify ethical principles guiding patient prioritization during disaster triage. Method: Electronic databases were searched via structured search strategy from 1990 until July 2017. The studies investigating patients' prioritization in disaster situation were eligible for inclusion. All types of articles and guidelines were included. Result: Of 7167 titles identified in the search, 35 studies were included. The important factors identified in patient prioritization were grouped into two categories: medical measures (medical need, likelihood of benefit and survivability) and Nonmedical measures (saving the most lives, youngest first, preserving function of society, protecting vulnerable groups, required resources and unbiased selection). Demographic characteristics, health status of patients, social value of patient, and unbiased selection are discriminatory factors in disaster triage. Conclusion: Various factors have been introduced to consider ethical patient prioritization in disaster triage. Providers' engagement, public education, and ongoing training are required to reach a fair decision.